Pembuatan Biogas Dari Kotoran Gajah - Anggoro Putra, I Ketut; Wijaya Kusuma, I.G.B.,; Adnyana, I.W. Bandem (Teknik Desain Mekanika, 2021)
Abstract Biogas is flammable gas that is produced from the fermentation process of organic materials by anaerobic bacteria. But for the formation of biogas it takes quite a long time, for 7 to 16 days. The formation of biogas is carried out by thermophilic bacteria during the day, because these bacteria can survive up to a temperature of 54,4°C. at night the formation is carried out by mesophilic bacteria with the optimal temperature for the formation of biogas at a temperature of 36,7ºC. In this research, elephant dung will be tested as a biogas material with a ratio of 1:1 with water. There are 4 tests to be carried out, the firs is a mixture of manure with water with the addition of dry straw and with a constant heating of 54°C, the second is a mixture of manure with water without straw and a constant heating of 54ºC, the third is a mixture of manure and water with addition of dry straw without heating, and the last mixture of manure with water without dry straw and without heating and carried out for 20 days. During 20 days of testing there was an increase in biogas in digester 1 on the first day with a formation rate of 15mm/day, in digester 2 there was an increase in biogas on the first day with a biogas formation rate of 13mm/day, in dogester 3 there was an increase in biogas on day 3 at a rate formation of 3mm/day, and in digester 4 there was an increase in biogas on day 3 with a formation rate of 2mm/day. It was found that the increase in digester 1 was better than in digester 2 digester 3 and digester 4 the increase remained constant because the temperature was kept constant. Keywords : Biogas, Elephant dirty.